Proceedings of the 33rd Annual ACM Conference on Human Factors in Computing Systems 2015
DOI: 10.1145/2702123.2702199
|View full text |Cite
|
Sign up to set email alerts
|

Texting while Parenting

Abstract: Child development research suggests that using phones while caring for children can be problematic, but limited prior work in this space makes defining appropriate use challenging. We conducted the first exploration of whether adults feel pressure to limit phone use in this context and whether they choose to do so. Through mixed methods, we collected data from 466 adult caregivers at playgrounds. We found that phone use was a small part of playground time, yet a notable source of guilt. Adults engaged in syste… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

6
49
2
8

Year Published

2017
2017
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 121 publications
(86 citation statements)
references
References 23 publications
6
49
2
8
Order By: Relevance
“…When researchers interviewed parents at Seattle-area playgrounds, for example, parents acknowledged that their phone use might reduce their attention to the world around them but also reported being able to easily reengage with their children when needed. The researchers' observations, however, conflicted with parents' optimistic perceptions: Parents who were using their phones frequently missed their children's bids for attention (Hiniker et al, 2015). These observations provide initial support for the idea that phone use may increase distraction in the context of parent-child interactions.…”
Section: Phone Use and Parentingmentioning
confidence: 81%
See 1 more Smart Citation
“…When researchers interviewed parents at Seattle-area playgrounds, for example, parents acknowledged that their phone use might reduce their attention to the world around them but also reported being able to easily reengage with their children when needed. The researchers' observations, however, conflicted with parents' optimistic perceptions: Parents who were using their phones frequently missed their children's bids for attention (Hiniker et al, 2015). These observations provide initial support for the idea that phone use may increase distraction in the context of parent-child interactions.…”
Section: Phone Use and Parentingmentioning
confidence: 81%
“…In the U.S., 95% of smartphone users admit to having used their smartphones during their latest social gathering (Rainie & Zickuhr, 2015)-a proportion that seems unlikely to extend to traditional media, such as newspapers and novels. And when researchers observed parents at Seattle playgrounds, they found that the majority used their smartphones (Hiniker et al, 2015). Although most used their phones fairly briefly, all of the parents who were interviewed had thoughts or concerns about phone use while spending time with their children, underscoring the need for rigorous research specifically on the effects of smartphones.…”
Section: Limitationsmentioning
confidence: 99%
“…Parent smartphone use has been associated with decreased responsiveness to children,(1) fewer verbal and nonverbal interactions,(2) and higher ratings of child externalizing behavior. (3) However, existing studies are limited by use of brief (10–15 minute) observations of parents using smartphones(1, 4) or rely on parent self-report,(3) which may be biased by social desirability. In addition, self-report of smartphone use may be inaccurate due to the brief, intermittent ways users interact with mobile devices,(5) which makes recall difficult.…”
Section: Introductionmentioning
confidence: 99%
“…Adding to a literature showing interruption of parent-child play by background television (Kirkorian, Pempek, Murphy, Schmidt, & Anderson, 2009), recent studies have suggested that parent mobile technology use around children is associated with fewer parent-child interactions (Radesky, Miller, Rosenblum, Appugliese, Kaciroti, & Lumeng, 2015a), lower responsivity to child bids (Hiniker, Sobel, Suh, Sung, Lee, & Kientz, 2015), and qualitative observations of parent hostility in response to child bids for attention (Radesky, Kistin, Zuckerman, Nitzberg, Gross, Kaplan-Sanoff, Augustyn, & Silverstein, 2014). Additionally, technological interruption during parenting has been associated with mothers’ perceptions of lower coparenting quality (McDaniel & Coyne, 2016b).…”
mentioning
confidence: 99%